Q-ball: high resolution fiber tractography of language associated tracts-quantitative evaluation of applicability for glioma resections - Becker, Daniela; Scherer, Moritz; Neher, Peter; Jungk, Christine; Jesser, Jessica; Pflüger, Irada; Bendszus, Martin; Maier-Hein, Klaus H.; Unterberg, Andreas (The journal of neurosurgical sciences, 2019)
BACKGROUND: To date, fiber tractography (FT) is predominantly based on Diffusion Tensor Imaging (DTI). High angular resolution diffusion imaging (HARDI)-based reconstructions have become a focus of interest, enabling the resolution of intravoxel fiber crossing. However, experience with high resolution tractography (HRFT) for neurosurgical applications is still limited to a few reports. This prospectively designed feasibility study shares our initial experience using an analytical q-ball approach (QBI) for FT of language-associated pathways in comparison with DTI-FT, focussing on a quantitative analysis and evaluation of its applicability in clinical routine. - METHODS: Probabilistic QBI-, and DTI-FT were performed for the major components of the language-associated fiber bundles (superior longitudinal fasciculus, inferior fronto-occipital fasciculus, medial/inferior longitudinal faciculus) in 11 patients with eloquent gliomas. The data was derived from a routine DWI sequence (b=1000s/mm2, 64 gradient directions). Quantitative analysis evaluated tract volume (TV), tract length (TL) and tract density (TD). Results were correlated to tumor and edema size. - RESULTS: Quantitative analysis showed larger TV and TL of the overall fiber object using QBI-FT compared with DTI-FT (TV: 16.45 ± 1.85 vs. 10.07 ± 1.15cm3; p<0.0001; TL:81.95 ± 6.14 vs. 72.06 ± 6.92 mm; p=0.0011). Regarding overall TD, DTI delivered significantly higher values (40.57 ± 6.59 vs. 60.98 ± 15.94 points/voxel; p=0.0118). Bland-Altman analysis illustrated a systematic advantage to yield lager TV and TL via QBI compared with DTI for all reconstructed pathways. The results were independent of tumor or edema volume. - CONCLUSIONS: QBI proved to be suitable for an application in the neurosurgical setting without additional expense for the patient. Quantitative analysis of FT reveals larger overall TV, longer TL with lower TD using QBI compared with DTI, suggesting the better depiction of marginal and terminal fibers according to neuroanatomical knowledge. This emphasizes the known limitation of DTI to underestimate the dimensions of a pathway. Rather than relying on DTI, sophisticated HRFT techniques should be considered for preoperative planning and intraoperative guidance in selected cases of eloquent glioma surgery.
Epub ahead of print
Gesehen am 07.04.2020